How ladder drill V-pattern and snake jump exercises impact the agility of basketball players - Custodio, Joselito M.; Shukla, Manish; Tulyakul, Singha; Taiar, Redha (Universitas Tanjungpura, 2024)
Background and Study Aim. Agility holds a pivotal role in basketball, influencing both defensive prowess and offensive maneuvers. This research delves into the impact of V-pattern ladder drill and snake jump exercises on basketball players' agility.Materials and Methods. Employing a quantitative methodology, this study adopts a Pre-Experimental design, specifically the Two Group Pretest-Post-test Design, executed across three stages. Utilizing purposive sampling, 15 male basketball athletes from Mariano Marcos State University were recruited as subjects. Data analysis, including normality and homogeneity tests, affirmed the data's appropriateness. Statistical analysis was facilitated using the SPSS 26 application.Results. The findings unveiled a notable enhancement in biomotor agility ability (p=0.005) following ladder drill training. These outcomes imply that incorporating ladder training with V-pattern and snake jumping can positively impact basketball players' agility, potentially enhancing their court performance.Conclusions. In conclusion, the statistical results underscore the effectiveness of ladder drill training with V-pattern and snake jumping in enhancing agility ability, thus advocating for its application in basketball training regimens.